Strategi Penerjemahan Kata Sapaan dengan Konteks Sosial dan Budaya dalam Novel Bumi Manusia Terjemahan Bahasa Inggris - Griselda Felicia Fredyryna Tumbole; Hayatul Cholsy (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study purposed to find the right translation strategy to overcome the problem of contextual addressing terms by analysing the translation strategy used in the Bumi Manusia novel by Pramoedya Ananta Toer, translated into This Earth of Mankind by Max Lane. The descriptive approach is used in this study to examine the translation strategy used in translating addressing terms enriched with social and cultural contexts. There are 990 addressing terms with 29 different names. According to data, six translation strategies are used, namely: (1) translation with more neutral/less expressive words is 51.3 percent of 508 data, (2) translation using loan words or loan with explanatory sentences is 35.9 percent of 355 data, (3) translation with cultural substitution is 7.2 percent of 71 data, (4) translation by omission is 5.4 percent from 53 data, (5) using more general words (superordinate) is 0.4 percent of 4 data, and (6) translations with paraphrase using an unrelated word is 0.2 percent of 2 data. Using the loan words or loan words with explanatory sentences can be qualified as one of the right strategies in overcoming the problem of the contextual meaning of the addressing terms in this novel.